Modification of Light to the Photosynthesis Rate of Hydrilla Sp with CaCO3 Concentration - Fhadillah, Afrizal Fahd; Krisdianto, Antonius; Aldiansyah, Muhammad Rafli; Nurul Millah, Siti Hafshoh (Ann Publisher, 2025)
This study aims to examine the effect of light modification on the rate of photosynthesis in Hydrilla sp. with varying CaCO3 concentrations. Light and calcium carbonate concentration are important factors that affect photosynthesis in aquatic plants. The study was conducted by modifying the intensity and duration of light and regulating the concentration of CaCO3 in the growing medium of Hydrilla sp. Photosynthesis rate was measured using experimental methods. The results showed that light modification had a significant effect on the rate of photosynthesis, with optimal light intensity and duration increasing photosynthesis. In addition, increasing CaCO3 concentration also increased the rate of photosynthesis, with a synergistic effect seen when light and CaCO3 were optimized together. This study concludes that light modification and CaCO3 concentration are important factors in increasing photosynthesis of Hydrilla sp., providing valuable insights for aquatic plant cultivation and aquatic ecosystem management.